2022
DOI: 10.48550/arxiv.2204.12511
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PolyLoss: A Polynomial Expansion Perspective of Classification Loss Functions

Abstract: Cross-entropy loss and focal loss are the most common choices when training deep neural networks for classification problems. Generally speaking, however, a good loss function can take on much more flexible forms, and should be tailored for different tasks and datasets. Motivated by how functions can be approximated via Taylor expansion, we propose a simple framework, named PolyLoss, to view and design loss functions as a linear combination of polynomial functions. Our PolyLoss allows the importance of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Previous studies have shown that [25] the first polynomial contributes more than half of the gradient in the later stage of training, highlighting the importance of the first polynomial. Better segmentation accuracy can be obtained by simply adjusting the first coefficient of the polynomial, without the need to adjust all polynomial coefficients 𝛼 𝑗 .…”
Section: Poly-dicelossmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies have shown that [25] the first polynomial contributes more than half of the gradient in the later stage of training, highlighting the importance of the first polynomial. Better segmentation accuracy can be obtained by simply adjusting the first coefficient of the polynomial, without the need to adjust all polynomial coefficients 𝛼 𝑗 .…”
Section: Poly-dicelossmentioning
confidence: 95%
“…Loss function is any differentiable function that maps predictions and labels to scalars. Existing studies have shown that [25] the accuracy of classification can be improved by applying the cross-entropy loss function to the Taylor expansion and adjusting the polynomial coefficient. Based on the loss function diceloss, which is commonly used in medical images, this paper proposed a loss function framework named poly-diceloss.…”
Section: Poly-dicelossmentioning
confidence: 99%
“…This advance avoids problems of model saturation and overfitting that traditional CNN encounters. Although different optimization techniques, such as dense connection and fine-tuning, are applied to further improve the model performance [47][48][49][50], they rest upon these building block and milestone developments of these CNN models.…”
Section: • Image-level Classificationmentioning
confidence: 99%
“…Important for our purposes, NCE+RCE has been successfully employed in computer vision applications, particularly in the very high noise regime. Overall, α-loss, focal loss, and NCE+RCE have all been shown to be robust to label noise in the training data, and hence comprise a strong representative subset of the robust loss function literature (for more examples, see [26], [27], [28], [29]). However, to the best of our knowledge, each of these loss functions have not been previously considered in the joint setting of training and test domain shift, which we argue is the real-world scenario addressed by our proposed AUGLOSS methodology.…”
Section: Loss Functions For Noisy Labelingmentioning
confidence: 99%